English Varieties: Students’ Perceptions through Their Multiculturalism Perspectives - Saini, Fadhlan (LP2M IAIN Sultan Amai Gorontalo, 2022)
This research aimed at finding out the students’ perceptions toward their awareness in multiculturalism and to reveal the correlation of their perceptions on the use of their English varieties. To obtain the data, it was employed mix-method design by going through some steps. Seen through qualitative side, it was utilized descriptive qualitative method in which the researcher figured out the description of students’ awareness of multiculturalism and its position to the use of their English varieties. Meanwhile, in quantitative side, the researcher employed the calculation of the questionnaire by passing the SPSS program to measure out correlation of them both. It was intended to figure out the calculation of the questionnaire results between both perceptions, if there was any relationship. Findings showed that their perceptions were vary. It can be seen by the reflection of their activities of the external and internal activities of their own. Those activities were linked to explain that, by having multicultural awareness, students could define the methodology in enhancing their expression of English varieties. Additionally, within these activities, students could try to socialize and expand their ability in expressing English language variety by confidently as well as pleasantly.